2019
DOI: 10.1186/s12888-018-1980-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the public’s profile of mental health literacy in China: a nationwide study

Abstract: BackgroundIn the wake of China’s massive economic development, attention has only recently turned to the enormous treatment gap that exists for mental health problems. Our study is the first comprehensive, national examination of the levels and correlates of the public’s ability to recognize mental illness in the community and suggest sources of help, setting a baseline to assess contemporary Chinese efforts.MethodsData were collected in China as part of the Stigma in Global Context – Mental Health Study (SGC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
3
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 39 publications
2
72
3
6
Order By: Relevance
“…Another finding observed in the present survey was that many participants were neutral in responding to these attitudinal exploration may indicate that they were possibly not fully aware of symptoms of mental illness, help seeking standard pathways and harmful effects of stigmatization concerning different aspects of global MH. Overall according to the present survey findings and results of other surveys, MHL of general community is deficient in some areas than the other and needs further improvement across the world [77,78]. Overall, the present survey identified several deficiencies in public knowledge, attitude and practice and future studies are called for improving public MHL in Saudi Arabia.…”
Section: Discussionsupporting
confidence: 56%
“…Another finding observed in the present survey was that many participants were neutral in responding to these attitudinal exploration may indicate that they were possibly not fully aware of symptoms of mental illness, help seeking standard pathways and harmful effects of stigmatization concerning different aspects of global MH. Overall according to the present survey findings and results of other surveys, MHL of general community is deficient in some areas than the other and needs further improvement across the world [77,78]. Overall, the present survey identified several deficiencies in public knowledge, attitude and practice and future studies are called for improving public MHL in Saudi Arabia.…”
Section: Discussionsupporting
confidence: 56%
“…GAD is the most common anxiety in primary health care and is associated with significant disease burden (27). According to the Stigma in Global Context -Mental Health Study conducted in China, less than one-third of people could recognize schizophrenia or depression in vignettes as a mental illness, while less than 20% of people could accurately recognize the specific disease (28). Less than 5% of patients first visited psychiatrists and over 70% of patients first visited nonmental health professionals in general hospitals, according to a study conducted in a general hospital (29).…”
Section: Introductionmentioning
confidence: 99%
“…Kilany (2018) found that healthcare utilization by individuals with severe mental illness in uences by medical insurance and urban-rural dispersal [32]. Huang and colleague's 2019 study nds that an individual's perception of a higher severity level indicates greater impetus for treatment [33].…”
Section: Discussion 1key Factors Determining Help-seeking Behavior Inmentioning
confidence: 99%